ANALISIS PENGEMBANGAN EKSPOR KOPI DI INDONESIA - Siska Fibriliani Sahat; Nunung Nuryartono; Manuntun Parulian Hutagaol (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2016)
This study aims to analyze recommendations that Indonesia could undergo to increase it’s coffee export performance through factors influencing it’s coffee export growth driver. The analysis using export decomposition showed that since 1994-2013, Indonesian coffee export has been dominated by commodity (grean bean). Export in the form of commodity is fragile regarding it’s volatile price in the international market. This lead to recommend higher processed coffee incorporated in Indonesian coffee export structure. At the same time, regarding the characteristics of the product, the diversification of Indonesian coffee product from green bean to coffee extract is in parallel with the destination country. Gravity model on top three destination countries for Indonesian coffee extract, namely Phillipines, China and Lebanon suggest that supply side, trade agreement and currency are the most influencing factors to trade, and that distance plays insignificant role.